Perancangan Ui/Ux Aplikasi B-Side: Marketplace Fashion Minor Defect Untuk Mendukung SDGS 12 - Savira Narita Rachman; Mochamad Rafi Djaenal Pratama; Muhammad Ikhlasul Amal Akbar; Arista Pratama (CV. SINAR HOWUHOWU, 2026)
This study designs the user interface and user experience (UI/UX) of the